Predictors of Clean Cookstoves Adoption by Households in Lagos State, Nigeria - Adebisi , S. A.; Johnson, F. O. (Unilag Journal of Humanities, 2019)
The adoption of Clean Cookstoves (CCS), which are clean, efficient, renewable and modern forms of cookstoves and fuels, have shown mixed results globally. In SubSaharan Africa, the adoption rate of CCS is still at the lowest level despite persistent deteriorating environmental conditions, rapid deforestation, climate change, health hazards and rising mortality rate of women and young children as a result of the use of traditional cookstoves and fuels. Several socio-economic, cultural, behavioural, institutional and environmental factors have been identified as critical factors influencing energy cooking choice of households across the urban and rural regions. Drawing from the value chain framework and relevant literatures, fourteen (14) predictive factors were identified as critical factors for the adoption of CCS and fuels in Lagos State, Nigeria. A survey of 200 households on their perception of CCS adoption in Lagos Mainland LGA of Lagos State was carried out. The outcome of responses was analysed using the Partial Least Square (PLS) Regression Technique. The results revealed that user’s preference, household’s affordability, CCS suitability, perceived benefits of using CCS, the transition to CCS, level of education and accessibility of CCS are strong predictors of the adoption of CCS by Lagos households; the remaining factors are low predictors. Additionally, the T-test results revealed that all the factors were significant at a 0.05, except for customs and belief which recorded a lower significant value. The study recommended that all the identified fourteen (14) predictors should be considered as the value-added interactions of factors are fundamental to the adoption of a new product or technology, however, the strong predictors identified in the study should be given utmost consideration.